Uncommon allele in APO AI-CIII-AIV gene cluster in a family with congenital generalized lipodystrophy - Novak, Estela Maria (1997)
Congenital generalized lipodystrophy is a rare inherited disease. One of its features is a disturbance in lipid metabolism characterized by hypercholesterolemia and hypertriglyceridemia. A brother and a sister with congenital generalized lipodystrophy, an 8-year old male and a 12-year old female were studied. The mother and a 6-year old brother were healthy. The genetic analysis of Sstl RFLP of the apo Al-CIII-AIV gene cluster showed the presence of the rare Sstl allele (S2) in the patients but not in the healthy mother and brother. As this uncommon allele has been reported to be related to high plasma triglyceride levels, this association could be relevant in explaining in part the hypertriglyceridemia observed in these patients.